2012
DOI: 10.1155/2012/731375
|View full text |Cite
|
Sign up to set email alerts
|

Rhizome Yield of Sweet Flag (Acorus calamusL.) as Influenced by Planting Season, Harvest Time, and Spacing

Abstract: A study was undertaken for two consecutive years to assess the possibility of optimizing rhizome yield ofAcorus calamusL. (sweet flag) by shifting the time of planting (i.e., growing in rainy and autumn seasons), maintaining different spacings, and harvesting in different months. Significantly higher yields of A. calamus were recorded when seeded in autumn (13150 kg ha−1) than rainy (6570 kg ha−1) season. Harvesting of crop after 12 months gave maximum rhizome yields of 16470 kg ha−1and 9370 kg ha−1respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The increase in yield under closer spacing may be ascribed due to the higher plant density per unit area. Similar findings were reported by Singh and Nongmaithem (2013) and Tiwari et al, (2012) on Acoruscalmus and Bisen et al, (2007) in ginger. Present study also showed that rhizome yield increased significantly with application oforganic and inorganic fertilizer i.e., 20-10-15kg/ha N-P 2 O 5 -K 2 O + Vermicompost (1t/ha) and was followed by application of 60-30-45 kg/ha N-P 2 O 5 -K 2 O.…”
Section: Rhizome Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in yield under closer spacing may be ascribed due to the higher plant density per unit area. Similar findings were reported by Singh and Nongmaithem (2013) and Tiwari et al, (2012) on Acoruscalmus and Bisen et al, (2007) in ginger. Present study also showed that rhizome yield increased significantly with application oforganic and inorganic fertilizer i.e., 20-10-15kg/ha N-P 2 O 5 -K 2 O + Vermicompost (1t/ha) and was followed by application of 60-30-45 kg/ha N-P 2 O 5 -K 2 O.…”
Section: Rhizome Yieldsupporting
confidence: 91%
“…Wider spacing led to less intra plant competition and because of it higher yield attributing characters were experienced in the present study. Similar results were experienced by Tiwari et al, (2012). application of 20-10-15kg/ha N-P 2 O 5 -K 2 O + Vermicompost (1t/ha).…”
Section: Growth and Yield Attributing Characterssupporting
confidence: 84%
“…Phytochemical studies conducted on the ethanolic extract of U. lagopoides have unveiled the presence of flavonoids, glycosides, proteins and phytosterols. These compounds offer diverse health benefits, aiding in the management of various health conditions like fever, cough and inflammation [12,13] .…”
Section: Uraria Lagopodioidesmentioning
confidence: 99%
“…The pharmacological effect of Acorus is mainly related to its ethereal oil, which also has some non‐trivial uses, for example as fish anesthetic to minimize handling stress and mortality in fish culture (Bhuvaneswari & al., 2015). Acorus calamus (sweet flag) is widely cultivated for medicinal, ornamental and other purposes (Lokesh, 2004; Tiwari & al., 2012; Imam & al., 2013; Chandra & Prasad, 2017; Shu & al., 2018) and belongs to the group of successful alien plants in Europe and North America (Wein, 1939; Thompson, 1995; Chytrý & al., 2008; Vinogradova & al., 2009; Lansdown & al., 2016). As indexed in Scopus, more than 1000 papers on Acorus have been published over the past 10 years, especially on chemical compounds extracted from plants of the genus (e.g., Jaiswal & al., 2015; Bai & al., 2022; Wang & al., 2023).…”
Section: Introductionmentioning
confidence: 99%